The effect of resolidification on preform optimized infiltration growth processed (Y, Nd, Sm, Gd)BCO, multi-grain bulk superconductor. (January 2017) - Pavan Kumar Naik, S.; Seshu Bai, V.
Highlights: Effect of the addition of (Nd, Sm, Gd)2 BaCuO5 inclusions on YBCO and resolidification effect was investigated. Microstructural features of the doped samples show the compositional segregation in the precipitates. Elemental analysis confirmed the compositions of different phases present in the (Y, RE)BCO composites. Resolidification process resulted in large fraction of non-superconducting phases. Abstract: Controlling the microstructure of superconductors by incorporating the flux pinning centers and reducing the macro-defects to improve high field performance is the topic of recent research. In continuation, the preform optimized infiltration growth (POIG) processed YBa2 Cu3 O7−δ (YBCO) system, Y-site substituted with three mixed RE (Nd, Sm, Gd) elements is investigated. 20 wt.% of (Nd, Sm, Gd)2 BaCuO5 were mixed with Y2 BaCuO5 and POIG processed in reduced oxygen atmosphere to obtain YNSG superconductor. No seed is employed for crystal growth; hence the processed samples are multi-grained. Microstructural and compositional investigations on YNSG revealed the presence of different phases in the matrix as well as in precipitates which are of the order of submicron to 4 μm. A large fraction of macro-defects (∼6% of porosity) was observed in the YNSG sample. For reducing the unwanted macro-defects and refine the non-superconducting precipitates, processed YNSG sample is pressed and resolidified (by infiltrating the liquid phases once again) in an argon atmosphere and the structural, microstructural, elemental and superconducting properties are compared with YNSG and undoped samples. Due to spatial scatter in superconducting critical temperatures, caused by the distribution of different REBCO unit cells in YBCO, superconducting transition curve is sharp in YNSG, whereas the resolidified sample showed the broad transition due to solidified liquid phases.